DE FIDE ORTHODOXA 36 COMO FUENTE DE FELIPE EL CANCILLER Y DE LA LECTURA ABRINCENSIS IN ETHICAM VETEREM. - Buffon, Valeria A. (Revista Española de Filosofía Medieval, 2025)
During the first half of the 13th century, there was an assimilation of the recently received writings of Aristotle. In this assimilation, an attempt was made to incorporate Aristotelian writings into a Christian structure of thought, to which they could not always be adapted. In this process, the De fide orthodoxa by John of Damascus played a very important role, being received with the authority of a sum of patristic theology and used as such in the discussions on free will that took place among the first great theologians, among whom Philip the Chancellor stands out. In this work, I will describe the interpretation of two authors from different areas, a theologian like Philip the Chancellor, and a Master of Arts, commentator on the Nicomachean Ethics. In this analysis, I will show two ways of incorporating and grasping the contributions of the great synthesizer of Greek patristics.